Trade-offs around the use of biomass for livestock feed and soil cover in dairy farms in the Alaotra lake region of Madagascar. (March 2015) - Naudin, K.; Bruelle, G.; Salgado, P.; Penot, E.; Scopel, E.; Lubbers, M.; de Ridder, N.; Giller, K.E.
Highlights: We explored trade-offs between CA and the size of the farm cattle herd. The degree of soil cover retained on CA plots had a very small effect on net farm income. Farmers benefited from CA through the use of multipurpose cover crops as forage. The milk market had a strong influence on the way CA can be implemented at field level. Abstract: Conservation agriculture (CA) is promoted as a promising technology to stabilize or improve crop yields in Africa and Madagascar. However, small-scale farmers face difficulties to retain soil cover, mainly because of competing uses for the biomass produced, especially to feed cattle. To explore the relation between dairy production and CA we developed an optimisation model at farm level. Our aim was to explore trade-offs between CA practices and the size of dairy cow herds. Our model includes three main components: the farm, the crops and the cattle herd. The optimisation was made on the total net income for three years. Biomass produced by cropping activities can either serve as mulch or to feed cows. We applied a constraint on the minimum soil cover % to keep at the end of each year for CA fields: from 30% to 95%. We simulated two scenarios of milk market: a small milk market with low forage price and an open milk market scenario with higher price of forage. Three prototypes of farms were simulated with different proportion and size of four kinds of field. These three prototypes were: medium-sized farm with hillsides dominating, medium-sized farm with paddy fields dominating and small-sized farm with hillsides. Changing the degree of soil cover to be retained on CA plots did not significantly modify the total net farm income. It was more strongly influenced by the characteristics of the milk market. In case of a limited milk market it was not profitable to have more than seven cows because the expenses were not compensated by animal production. When setting minimum soil cover to 30% then all of the simulated results include biomass coming from CA cropping system even with 12 cows/farm. Conversely when setting this constraint to 95%, above 6/7 cows/farm forage come only from conventional fields. In all of the situations simulated even with 6 cows, with the current and twice the price for forage, it was possible to keep at least 50% of soil cover on 30–60% of the total farm area. CA was not feasible for farms with no irrigated paddy fields or when forage fetched a high price regardless of the constraint for % of soil cover to be kept on CA fields. Overall, CA systems can be beneficial for dairy cow farmers due to the forage produced, although the milk market and thus the value of biomass for forage, has a strong influence on CA practice at field level.